HUBUNGAN PENGGUNAAN MEDIA YOUTUBE TERHADAP KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA DALAM PEMBELAJARAN MATEMATIKA DI MIN 2 KUNINGAN - Dessy Ahsan; Anas Salahudin; Dede Rohaniawati (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
The outbreak of the Corona Virus Disease Pandemic or better known as COVID-19 has caused several changes in aspects of life throughout the world, including changes in aspects of education in Indonesia. In the educational aspect, this condition requires teachers and students to interact through online media. The basic objectives of this study are to see (1) how the use of youtube media in learning mathematics at MIN 2 Kuningan, (2) how students' higher order thinking skills in learning mathematics at MIN 2 Kuningan and (3) how the relationship between the use of youtube media on thinking skills high level of students in learning mathematics at MIN 2 Kuningan. The approach in this research is a quantitative approach. The data figures are obtained from the results of statistical analysis using SPSS 20 for windows. The method uses the correlation method with the type of quantitative descriptive research data. The research location is Madrasah Ibtidaiyah Negeri (MIN) 2 Kuningan. The results of this study (1) The use of Youtube media in learning mathematics at MIN 2 Kuningan is Potential by 69.45% in the Good category, Practical by 69.43% in the Good category, Informative by 78.86% in the Good category, Interactive by 74% in the Good category, Shearable at 74.77% in the Good category, and Economical by 67.5% in the Good category. (2) High-Level Thinking Ability of Students in Mathematics Learning in grade 5 MIN 2 Kuningan from the average student who is able to answer questions with operational verb analyze (C4) is 65.9% Good category, operational verb evaluates (C5) is 58 ,82% in the Enough category, operational work creates (C6) by 59.66% in the Enough category. (3) There is a positive relationship between Youtube media and higher-order thinking skills which are in the category of Medium relationship level of 0.476 with a relationship effect value of 22.7%.